Globalization and labour rights : the conflict between core labour rights and international economic law - Breining-Kaufmann, Christine (Studies in international trade law, 2007)
In a world of work that has changed dramatically over the last few years, states see themselves confronted with new actors and conflicting international legal obligations. This book examines the tensions between core labour rights as defined by the International Labour Organisation, and the interests of international economic institutions (e.g. WTO, IMF, World Bank, OECD). It provides an analysis of the legal interactions between international regulations and state policy with regard to potential regulatory conflicts, at both the horizontal and vertical level. The study suggests a model of multilevel consistency as a way of reconciling the highly specialised and fragmented legal systems of core labour rights on the one hand, and trade liberalisation on the other, to form the coherent framework of a consistent legal order.